Enhance the Properties of Lignosulfonate Mud by Adding Nanoparticles of Aluminum Oxide and Iron Oxide - Alasaly, Hasan Ali Abbood; Ibtehal Kareem Shakir (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Oil well drilling fluid rheology, lubricity, swelling, and fluid loss control are all critical factors to take into account before beginning the hole’s construction. Drilling fluids can be made smoother, more cost-effective, and more efficient by investigating and evaluating the effects of various nanoparticles including aluminum oxide (Al2O3) and iron oxide (Fe2O3) on their performance. A drilling fluid’s performance can be assessed by comparing its baseline characteristics to those of nanoparticle (NPs) enhanced fluids. It was found that the drilling mud contained NPs in concentrations of 0,0.25, 0. 5, 0.75 and 1 g. According to the results, when drilling fluid was used without NPs, the coefficient of fraction (CoF) was 44%, when added Al2O3 NP and Fe2O3 NP at 0.75g reduced CoF by 31% and 33% respectively. When Al2O3 and Fe2O3 NPs were used, particularly at a concentration of 1g, the amount of mud filtration decreased from 13.5ml to 9.3 ml and 8.5 ml respectively. Additional improvements rheological properties as well as swelling when Fe2O3NPs and Al2O3 NPs were added at 1g. Overall, it was found that adding NPs to the Lignosulfonate-WBM at a concentration of 1g can improve rheological, swelling, and filtration properties as well as lubrication at 0.75g.